Morphological and Anatomical Properties of Himalayan Herb Stellaria webbiana - Chandra, Satish; Rawat, D. S. (International Journal of Environment, 2016)
Stellaria webbiana is a Himalayan endemic herb, distributed in Central and Western Himalaya. The present study is based on the morphological properties, anatomical properties and seed microstructure of the species. Number of valves in mature fruit, anatomical properties, stomata type, trichomes, seed microstructure and Western most limit of the species in the Himalaya is described first in the present study. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-2, March-May 2016, Page:26-35